Campaign Against Pit Closures - Nalgo poster, 1992 (London, 1992)
1992 1980-95 "Campaign Against Pit Closures - Nalgo poster, 1992" [BW0146], 1992, Trades Union Congress On October 13, 1992, the Government announced that 31 of British Coal's remaining pits would close with the loss of 30,000 jobs. The National Union of Mineworkers launched a campaign against the closures which gained widespread public support, but which in the end was generally unsuccessful in securing the future of the coal industry. This poster was produced by the National and Local Government Officers Association